Optimization Design and Simulation Analysis of Cycloid Pin Gear Planetary Reducer - Liang Kaixiang; Wang Zhongsu; Tian Shitao; Wu Qingwen; Xu Zhenbang (Jixie chuandong)
The cycloid pin gear reducer has the characteristics of small size,large output torque,and widely used in robotic joints. A set of equations is presented to optimize the cycloid pin gear reducer with pillow needle tooth structure instead of the cantilever type tooth structure,which is of compact and high strength. A genetic algorithm is used to optimize the structural parameters of reducer. The smallest volume,minimum mass and maximum efficiency are set as objective functions,the relevant constraints conditions are derived on the basis of Hertz formula,etc. On this basis,the optimization of reducer key structure parameter is carried out,and the simulation analysis is carried out by using the finite element method. The results show that the reducer meets the design requirements,the optimization is valid and valuable on engineering application.